2018
DOI: 10.2147/cmar.s167330
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A promotes GLI1 degradation and P21 expression in multiple myeloma cells

Abstract: BackgroundHistone deacetylase inhibitors are promising drugs for the future application in cancer therapy. Trichostatin A (TSA), a histone deacetylase inhibitor, exhibits effective antitumor effects in various cancers. However, the effects and underlying mechanisms of TSA on multiple myeloma (MM) are not fully investigated.MethodsIn the present study, RPMI8226 and MM.1S cells treated with TSA were used for cell proliferation, cell cycle, and survival examinations, then the localization and post transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Remarkably, HDAC6 effects seem to be independent of GLI acetylation, and to occur most likely through the transcriptional control of GLI2 expression and stabilization of GLI3 protein (Dhanyamraju et al, 2015). In line with these findings, a recent study in multiple myeloma revealed that hyper-acetylation of GLI1 through pharmacological inhibition of class I and II HDACs leads to reduced tumor survival by decreasing nuclear accumulation and transcriptional activity of GLI1, and accelerating its proteasomal degradation (Geng et al, 2018).…”
Section: Non-canonical Activation Of Gli Transcription Factors In Canmentioning
confidence: 74%
“…Remarkably, HDAC6 effects seem to be independent of GLI acetylation, and to occur most likely through the transcriptional control of GLI2 expression and stabilization of GLI3 protein (Dhanyamraju et al, 2015). In line with these findings, a recent study in multiple myeloma revealed that hyper-acetylation of GLI1 through pharmacological inhibition of class I and II HDACs leads to reduced tumor survival by decreasing nuclear accumulation and transcriptional activity of GLI1, and accelerating its proteasomal degradation (Geng et al, 2018).…”
Section: Non-canonical Activation Of Gli Transcription Factors In Canmentioning
confidence: 74%
“…The treatment of trichostatin A in MM cells led to alterations in H3K4 methylation [21]. After treatment with trichostatin A, the proliferation inhibition of MM cells was found via GLI1 degradation and P21 overexpression, and this proliferation inhibitory effect had a time- and dose-dependent character [22]. The result of the molecular docking between trichostatin A and CDK1 may reveal a new mechanism for the action of trichostatin A in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Among the HDACs, HDAC1 is a positive modulator of activator members of the GLI family (Canettieri et al, 2010). GLI1 physically interacts with HDAC1, and HDAC1‐mediated deacetylation of GLI1 results in its transcriptional activity (Canettieri et al, 2010; Falkenberg et al, 2016; Geng et al, 2018; Gurung et al, 2013). GLI1 deacetylation leads to the growth of medulloblastoma (Canettieri et al, 2010) and is increased in resistant basal cell carcinomas (Mirza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%